Fabrication of semiconductor lasers with pulsed anodic oxidation - Liu, Chong Yang. (2008)
The report will discuss the experimental investigation that are related to the semiconductor laser fabrication with pulsed anodic oxidation. Beside semiconductor laser fabrication, correlative characteristics of each material system were also specially studied in order to improve their corresponding laser diode performance.